2018
DOI: 10.3390/w10091145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Factors in Agricultural Production on the Crop Water Footprint in Xinjiang, China

Abstract: Irrigation plays an important role in China’s agricultural production, and a reasonable assessment of water resources consumption in agricultural production will contribute to improved agricultural water management practices. The objectives of this study were to analyze variations in the magnitude of the crop water footprint (CWF) in Xinjiang and determine the major factors that influence variation in order to provide proposals for water resources management. The CWF of Xinjiang from 1988 to 2015 was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…The third limitation is that this paper did not distinguish groundwater and surface water within the blue PW consumption by all sectors. According to the statistics, groundwater consumption by economic production within the NTM increased from 3.976 km 3 in 2006 to 6.599 km 3 in 2016, indicating that there is a rapidly increasing exploitation of groundwater in the NTM by economic production [41]. Therefore, future studies should distinguish between the dependence of local economic sectors on surface water and groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…The third limitation is that this paper did not distinguish groundwater and surface water within the blue PW consumption by all sectors. According to the statistics, groundwater consumption by economic production within the NTM increased from 3.976 km 3 in 2006 to 6.599 km 3 in 2016, indicating that there is a rapidly increasing exploitation of groundwater in the NTM by economic production [41]. Therefore, future studies should distinguish between the dependence of local economic sectors on surface water and groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…Hoekstra and Mekonnen (2012) estimated that the water footprint used for global agricultural production is approximately 7106 Gm 3 /a, including blue water footprint at 920 Gm 3 /a and green water footprint at 6186 Gm 3 /a [16]. The research results of Zhang et al (2018) indicated that more than 90% of the agricultural production water footprint was dependent on the blue water footprint in Xinjiang Province [17]. Thus, the water resource volume, available water resource volume and irrigation water volume are all unilaterally used as characteristic parameters of the water resource consumption of a region, and the matching situation should be considered from the perspective of the blue-green production water footprint.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have studied the impact of irrigation techniques, irrigation strategies and field water management policies on blue-green-grey water footprints through experimental observation and model simulation [31][32][33]. In addition, the driving mechanism of multiple factors, such as cropplanting structures, area of irrigation, agricultural inputs, and water conservancy projects, on regional crop water footprints have also received attention [21,34]. These studies have provided important and useful information for reducing and regulating the water footprint for specific crops.…”
Section: Introductionmentioning
confidence: 99%